Granulocyte collections: comparison of two apheresis systems. Issue 12 (15th April 2013) - Thorausch, Kristin; Schulz, Miriam; Bialleck, Heike; Luxembourg, Beate; Seifried, Erhard; Bonig, Halvard
<x xml:space="preserve">Abstract</x> Background Donor granulocyte concentrates are routinely administered to patients with granulocyte function defects or transient neutropenia and (risk of) bacterial or fungal exacerbations, despite lack of definitive clinical proof for patient‐relevant outcome improvement. Granulocytes are collected by apheresis from healthy donors treated with granulocyte–colony‐stimulating factor and/or steroids for neutrophil mobilization the evening before apheresis, as well as with hydroxyethyl starch during apheresis, to enhance sedimentation of red blood cells (RBCs) and thus to facilitate accessibility of neutrophils for collection. Study Design and Methods Granulocyte apheresis procedures are performed with standard apheresis equipment, including with the frequently used apheresis system for peripheral blood "stem cell" collection, COBE Spectra MNC (Terumo BCT), using the same tubing set as for MNC collection, but a different software protocol, PMN. An automated apheresis system for granulocyte collection, Spectra Optia IDL (Terumo BCT), became available in October 2011. Since then, 70 granulocyte apheresis procedures have been performed at our site, 35 each with the new and old systems. Results Apheresis procedures were well tolerated throughout. The target dose of 1 × 1010 neutrophils was achieved in all but one collection with Spectra Optia IDL. Spectra Optia IDL collections were approximately 20% more efficient. Products contained more nontarget white blood cells (mononuclear cells), but fewer RBCs and platelets. Although less blood had to be processed with Spectra Optia IDL to achieve the same granulocyte dose, clinically relevant differences between the two apheresis devices were not apparent. Conclusion Both apheresis systems are similarly capable of generating granulocyte concentrates.